Chemical and texture characteristics and sensory properties of “mozzarella” cheese from different feeding systems - R. Rubino; M.V. Schettino; E. Sabia; M. Pizzillo; E. Agoglia; S. Claps (Italian Journal of Animal Science, 2010)
The aim of this study was describing the chemical composition, the rheological characteristics and the sensory properties of “mozzarella” cheese produced with milk from buffalos fed with different diets. The study involved two farms and four feeding systems. In farm C, one group was mostly fed with Ryegrass Hay (RH) and the other group with Ryegrass Silage (RS). In farm T, instead, one group was mostly fed with Corn Silage (CS) and the other one with a Sorghum Silage (SS). In summer, three cheesemakings, for each farm and for each feeding system, were carried out at C.R.A. of Bella. In each farm, data were processed by the analysis of variance in order to compare the effects of two feeding systems. Some parameters of chemical and texture characteristics and sensory properties were influenced by the feeding system. Results were remarkable for the DOP products.